How COVID-19 induces cytokine storm with high mortality - Shintaro Hojyo; Mona Uchida; Kumiko Tanaka; Rie Hasebe; Yuki Tanaka; Masaaki Murakami; Toshio Hirano (BMC, 2020)
Abstract The newly emerging coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) was first reported in Wuhan, China, but has rapidly spread all over the world. Some COVID-19 patients encounter a severe symptom of acute respiratory distress syndrome (ARDS) with high mortality. This high severity is dependent on a cytokine storm, most likely induced by the interleukin-6 (IL-6) amplifier, which is hyper-activation machinery that regulates the nuclear factor kappa B (NF-κB) pathway and stimulated by the simultaneous activation of IL-6-signal transducer and activator of transcription 3 (STAT3) and NF-κB signaling in non-immune cells including alveolar epithelial cells and endothelial cells. We hypothesize that IL-6-STAT3 signaling is a promising therapeutic target for the cytokine storm in COVID-19, because IL-6 is a major STAT3 stimulator, particularly during inflammation. We herein review the pathogenic mechanism and potential therapeutic targets of ARDS in COVID-19 patients.